Influence of root secretions of understory Chinese herbal medicines on the characterization of inter-root microbial communities - Yang, Yuan; Li, Jianqiang; Yang, Bo; Wang, Linling; Tang, Wenqi; Cha, Lianling (Frontiers in Plant Science, 2026)
The root exudates of Chinese medicinal herbs under the forest play a crucial regulatory role in the rhizosphere microbial community. This study systematically revealed the chemical characteristics of root exudates from Panax notoginseng, Polygonatum sibiricum, and Eutrema wasabia under the forest and their differential impact mechanisms on the rhizosphere microbial community. Research has found significant species specificity in the types and quantities of root exudates from three plants. A total of 329, 250, and 193 differential compounds were identified in P. notoginseng, P. sibiricum, and E. wasabia, respectively. Among them, P. notoginseng and E. wasabia share 165 compounds, both of which are mainly composed of lipids and organic acids. However, the specific types and proportions vary, reflecting their unique ecological functions and pharmacological effects. Root exudates significantly regulate the structure and diversity of microbial communities, with Proteobacteria, Acidobacteria, and Basidiomycota being dominant groups. Mantel’s test confirmed that the main components of secretions are significantly positively correlated with the abundance and diversity of microbial communities. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis further showed that different plants adapt to the environment by activating differentiated metabolic pathways (22 enriched in P. notoginseng, 20 enriched in P. sibiricum, and 15 enriched in E. wasabia). More importantly, the microbial metabolite interaction network analysis revealed processing specificity: specific bacteria in the P. notoginseng forest were strongly positively correlated with lipids, and fungi with phenolic metabolites, while P. sibiricum and E. wasabia forests showed a completely different association pattern, regulating the accumulation of key metabolites such as lipids, phenols, and oligosaccharides by reshaping the network. These findings provide key evidence for understanding the microbial-driven mechanisms underlying the quality formation of medicinal plants, emphasizing the importance of optimizing root exudate management to enhance soil microbial health and promote sustainable agricultural development.